Answer:
The average rate of change of the function
over the interval
is -1
Explanation:
We are given the function
over the interval
![-11 \leq x\leq -1](https://img.qammunity.org/2021/formulas/mathematics/high-school/t3ubmtnif78yz9oqm37wu96vszdibi6gx5.png)
We need to find average rate of change.
The formula used to find average rate of change is :
![Average \ rate \ of \ change=(g(b)-g(a))/(b-a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5hnahyyz7e11yhbyqwugusvj2lc545pww5.png)
We have b=-1 and a=-11
Finding g(b) = g(-1)
![g(x)=x^2+10x+18\\Putting \ x=-1\\g(-1)=(-1)^2+10(-1)+18\\g(-1)=1-10+18\\g(-1)=9](https://img.qammunity.org/2021/formulas/mathematics/high-school/gs1ohkwgzvppsc56beea8d5el242qvwqun.png)
Finding g(a) = g(-11)
![g(x)=x^2+10x+18\\Putting \ x=-11\\g(-11)=(-11)^2+10(-11)+18\\g(-1)=121-110+18\\g(-1)=29](https://img.qammunity.org/2021/formulas/mathematics/high-school/uh6y6r11qjgr5j7x4e0y4u1komikfax95q.png)
Finding average rate of change
![Average \ rate \ of \ change=(g(b)-g(a))/(b-a)\\Average \ rate \ of \ change=(9-29)/(-1-(-11))\\Average \ rate \ of \ change=(-10)/(-1+11)\\Average \ rate \ of \ change=(-10)/(10)\\Average \ rate \ of \ change=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/y435id1t3yr24xowg5pk9wbzwbsd0fr89a.png)
So, the average rate of change of the function
over the interval
is -1